2022
DOI: 10.1093/mnras/stac2714
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the SN Ia host galaxy dust law distribution and mass step: hierarchical BayeSN analysis of optical and near-infrared light curves

Abstract: We use the BayeSN hierarchical probabilistic SED model to analyse the optical–NIR (BVriYJH) light curves of 86 Type Ia supernovae (SNe Ia) from the Carnegie Supernova Project to investigate the SN Ia host galaxy dust law distribution and correlations between SN Ia Hubble residuals and host mass. Our Bayesian analysis simultaneously constrains the mass step and dust RV population distribution by leveraging optical–NIR colour information. We demonstrate how a simplistic analysis where individual RV values are fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…SNe probe extinction much more precisely than our spatially averaged measurements, approaching the point-source probes provided by ordinary stars. Thorp & Mandel (2022) used a hierarchical Bayesian approach to address the possibility of unphysical ranges of R retrieved in SN samples due to observational error, finding R = 2.2-2.6 for Type Ia SNe in the Carnegie Supernova project. They contrast this with R = 1.9 from fits to individual SNe from Johansson et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…SNe probe extinction much more precisely than our spatially averaged measurements, approaching the point-source probes provided by ordinary stars. Thorp & Mandel (2022) used a hierarchical Bayesian approach to address the possibility of unphysical ranges of R retrieved in SN samples due to observational error, finding R = 2.2-2.6 for Type Ia SNe in the Carnegie Supernova project. They contrast this with R = 1.9 from fits to individual SNe from Johansson et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses have found conflicting results. By measuring 𝑅 𝑉 for individual SNe Ia using a hierarchical Bayesian model, Thorp et al (2021) and Thorp & Mandel (2022) found no significant difference in the 𝑅 𝑉 population means between SNe in low and high mass galaxies. There is also some evidence that the step remains when measuring distances using near infra-red (NIR) light curves, where the effects of dust should have a smaller impact (Ponder et al 2021;Uddin et al 2020;Jones et al 2022), although, by contrast, Johansson et al (2021) found the step was removed in both the NIR and when fitting each SN Ia for its 𝑅 𝑉 .…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, recent cosmological studies utilizing SN Ia have proposed host stellar mass as a third parameter (Kelly et al 2010), in addition to the light curve shapes (Phillips 1993) and color (Tripp 1998), for the standardization of SN Ia distance (Hamuy et al 1995;Lampeitl et al 2010;Childress et al 2013a), despite the question as to whether it is an intrinsic property or just an effect of dust (Johansson et al 2021;Thorp & Mandel 2022). Although it is not to be addressed here, exploring the star formation-activity-related luminosity functions and mass functions may offer an alternative perspective.…”
Section: Introductionmentioning
confidence: 99%